An investigation of teaching, social and cognitive presence in online learning - Azizul Hassan, Aini Faridah; Ahmad Basri, Noraini; Ismail, Othman; Rahmat, Noor Hanim; Abdul Latif @ Bapoo, Lilisuriani (Human Resource Management Academic Research Society, 2023)
The purpose of this investigation was to explore the Community of Inquiry model (CoI) elements of teaching, social, and cognitive presence were mostly present in online learning environments. A quantitative approach was employed, and data were collected via survey from eighty-nine respondents. The findings revealed that teaching presence was the most influential element and evident in the design and facilitation of the courses, as instructors provided clear instructions and timely feedback. Social presence was evident through the use of discussion forums and group projects, which allowed students to interact and build relationships with one another. Finally, cognitive presence was evident through the use of reflective activities and challenging assignments, which encouraged students to think critically and engage with the course material. Overall, the results suggest that a balance of teaching, social, and cognitive presence is essential for effective online learning environments. Instructors should design courses that promote interaction and collaboration among students, provide clear instructions and feedback, and incorporate activities that encourage students to think deeply about the course material.